Vegetation history and human activity during the last 6000 years on the central Catalan coast (northeastern Iberian Peninsula) (Vegetation History and Archaeobotany, 1994)
In this paper, we present the results of four pollen diagrams obtained from the northeastern coast of the Iberian Peninsula. These data, together with a set of 11 radiocarbon dates, allow us to make some suggestions about human activity in this area mainly during the last 6000 years. We have established four main stages of this activity. Phase I (7000-3000 B.P.) shows some sporadic human clearance without qualitative and/or quantitative changes inside the natural woodland, except for slight oscillations in AP values. These clearances are synchro- nous with Neolithic and Bronze Age settlements. Phase II (3000-1500/1300 B.P.) demonstrates a different hu- man action on the landscape along the Catalan coast. Sampling sites located in rich agricultural plains and close to urban centres show continuous woodland clear- ance during the Iberian period and especially during Ro- man times. In contrast, at boring sites far from these towns, the irregular and sporadic woodland disturbances continue, although these become more common. Phase III (1500/1300-850 B.P.) shows further woodland clear- ance fires along the coast. Pollen, archaeological and historical evidence allow us to relate this to the introduc- tion of grazing in the coastal area, connected with sea- sonal transhumance between the littoral and mountain regions. Phase IV (850-300/150 B.P.) is characterised by the final clearance of woodland and the development of olive farming. During this phase the agrarian Mediterra- nean landscape was definitively formed.